2024
DOI: 10.3389/fpls.2023.1304388
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model genome-wide association studies for appearance quality in rice

Supriya Sachdeva,
Rakesh Singh,
Avantika Maurya
et al.

Abstract: Improving the quality of the appearance of rice is critical to meet market acceptance. Mining putative quality-related genes has been geared towards the development of effective breeding approaches for rice. In the present study, two SL-GWAS (CMLM and MLM) and three ML-GWAS (FASTmrEMMA, mrMLM, and FASTmrMLM) genome-wide association studies were conducted in a subset of 3K-RGP consisting of 198 rice accessions with 553,831 SNP markers. A total of 594 SNP markers were identified using the mixed linear model meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…By combining the information reported at the Gramene ( http://www.gramene.org/markers/ ), BLAST ( http://blast.ncbi.nlm.nih.gov/Blast.cgi ), and China Rice Data Center database ( http://www.ricedata.cn/gene/list/1499.htm ) websites, the QTLs identified in this study were compared with those reported previously for controlling the DEC/PGWC. We compared the results identified in this study with those reported previously by Misra et al (2019 , 2021) and Sachdeva et al (2024) and found that none of the identified loci were common, which could be related to the large differences in the geographical origins and characteristics of the varieties used. The varieties used by Misra et al (2019 , 2021) and Sachdeva et al (2024) included indica, aus, tropical japonica from the IRRI South Asia Regional Center, Varanasi, Uttar Pradesh, India, whereas the materials used in this study included indica mainly from South China, East China, Central China, Vietnam, Philippines, and Indonesia as well as temperate japonica rice from East China, North China, and Northeast China.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…By combining the information reported at the Gramene ( http://www.gramene.org/markers/ ), BLAST ( http://blast.ncbi.nlm.nih.gov/Blast.cgi ), and China Rice Data Center database ( http://www.ricedata.cn/gene/list/1499.htm ) websites, the QTLs identified in this study were compared with those reported previously for controlling the DEC/PGWC. We compared the results identified in this study with those reported previously by Misra et al (2019 , 2021) and Sachdeva et al (2024) and found that none of the identified loci were common, which could be related to the large differences in the geographical origins and characteristics of the varieties used. The varieties used by Misra et al (2019 , 2021) and Sachdeva et al (2024) included indica, aus, tropical japonica from the IRRI South Asia Regional Center, Varanasi, Uttar Pradesh, India, whereas the materials used in this study included indica mainly from South China, East China, Central China, Vietnam, Philippines, and Indonesia as well as temperate japonica rice from East China, North China, and Northeast China.…”
Section: Discussionmentioning
confidence: 71%
“…We compared the results identified in this study with those reported previously by Misra et al (2019 , 2021) and Sachdeva et al (2024) and found that none of the identified loci were common, which could be related to the large differences in the geographical origins and characteristics of the varieties used. The varieties used by Misra et al (2019 , 2021) and Sachdeva et al (2024) included indica, aus, tropical japonica from the IRRI South Asia Regional Center, Varanasi, Uttar Pradesh, India, whereas the materials used in this study included indica mainly from South China, East China, Central China, Vietnam, Philippines, and Indonesia as well as temperate japonica rice from East China, North China, and Northeast China. The results obtained in this study were also compared with those reported previously by Xin et al (2022) , and none of the loci identified were common; this may be attributed to the fact that the genetic backgrounds of the materials used were very different.…”
Section: Discussionmentioning
confidence: 71%